Energy Aware Congestion Adaptive Reactive Routing Protocol with Link Quality Monitoring - Singh, JK; Kalla, M (International Journal of Computer Sciences and Engineering, 2025)
In MANETs, packet delivery from source to destination is a complex task as many factors affect the network performance. The major factors in routing are node mobility, node energy and congestion in the wireless bandwidth limited channel and battery operated nodes with dynamic topology. This paper proposes a cross-layer based feedback among different layers, namely physical, MAC and network to pass the link information from physical to network layer. The Cross-Layer design approach helps checking the link condition as well as energy and congestion status to select the optimal path between source and destination. The proposed energy aware congestion adaptive reactive routing protocol with link monitoring (EACARP-LM) also finds alternate path proactively before the link breaks due to mobility, becomes heavily congested or an intermediate node exhaust its battery power. The protocol uses energy monitor, congestion monitor and link monitor for monitoring the respective parameter during the node operations. Based on these monitors the node takes decision for transmitting the packets and selecting a new route for packet delivery. This cross-layer design approach is implemented in Network simulator (NS2 simulator) and its performance is compared with the traditional AODV routing protocol, which indicates the better QoS parameters and increased network life time.